Cytology history in patients with invasive carcinoma of uterine cervix - Jerónimo, José (2015)
OBJECTIVES: To determine if the Pap smear decreases the risk of developing invasive cervical cancer and cytological features history of patients with invasive cervical cancer. DESIGN: Descriptive, transversal. LOCATION: Department of Gynecology and Obstetrics of Mary Help Support Hospital. MATERIALS AND METHODS: cytological screening of 59 patients with histologically confirmed invasive cervical carcinoma and 155 with squamous intraepithelial lesion high grade (LEI-AG), seen between January 1997 and September 1998. RESULTS: Of the patients invasive cancer, 53.4% had never had cytology and 65.5% of patients had no PAP or the last study was conducted for more than five years; 31% of patients had gynecologic evaluation and negative PAP in the last three years. Of patients with squamous intraepithelial lesions of high grade (LEI-AG), 35.2% had never done a PAP or had had for more than five years ago and 54.2% had negative clinical and cytologic evaluation in past three years, with statistical significance (p <0.005] CONCLUSIONS: The cytology Papanicolaou method protects women from developing invasive lesions of cervical cancer can be assumed that a group of patients with cervical cancer and had changes at the cervix. which may have been previously detected, either by clinical examination or by cytology.